THE FUNCTION OF LAW IN ECONOMIC DEVELOPMENT AND COMMUNITY EMPOWERMENT IN INDONESIA - Thamrin, Husni; Thamrin, Muhammad Arganata; Sobirov, Bobur; Royani, Esti (Awang Long Law Review, 2024)
The purpose of this study is to analyze the function of law in the stages of economic development and to analyze community empowerment through the role of law. The research is normative-legal research, using the statute approach, conceptual approach, and case approach. Secondary Legal Materials are all publications on a law that are not official documents which include textbooks, legal dictionaries, legal journals, and research reports. The collected legal materials are then analyzed qualitatively. The results of the research show that development in the economic field cannot work alone, but requires support from various parties, especially in the field of law. Law has a very central role in the success of a country's economic development, particularly in providing business and investment certainty, both at the central and regional levels. This will provide a huge opportunity for the central government in accelerating policies related to the economy in the regions because the regions are already stable in terms of the functioning of the legal function in the field of economic development. In relation to community empowerment, the function of law is as a driving force for development. In this case, the law as a tool to bring society in a more advanced direction will work dynamically following economic developments. Improvements in all sectors, starting from education, accessibility, action, institutions, business, income, environment, and life, and improving social relations in society will have a very big impact on economic growth in Indonesia.